Memorandum of understanding between Universiti Teknologi MARA and Chiang Mai University / Fakulti Perladangan dan Agroteknologi - Universiti Teknologi MARA, Fakulti Perladangan dan Agroteknologi (Universiti Teknologi MARA (UiTM), 2019)
Memorandum of understanding on friendship and cooperation for the purpose of promotion mutual understanding and academic, culture, scientific and personnel exchange.